Significance of Palatal Rugae in Orthodontics (Journal of Orofacial Research, 1970)
The palatine rugae have interested orthodontists not only because of their typical pattern of orientation but also because of their usefulness as a reference landmark in various dentaltreatment modalities. The pattern of orientation is formed by the 12th to 14th weeks of prenatal life and remains stable until the oral mucosa degenerates after death. The palatine rugae possess unique characteristics that could be used in circumstances in which it is difficult to identify a dead person according to fingerprints or dental records. Palatine rugae are permanent and unique to each person, and clinicians and scientists can use them to establish identity through discrimination. If particular rugae patterns could be established for different ethnic groups, they would assist the forensic odontologist in the identification of a person. Because they are a stable landmark, the palatine rugae also can play a significant role in clinical orthodontics.